1996
DOI: 10.1177/0361198196152900107
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Highway Work Zone Crashes: What We Know and What We Don't Know

Abstract: Emphasis on work zone safety and improving the identification of work zone problems has been increased by recent legislation and federal programs. There is a critical need for better data related to highway work zone safety. Results are presented of an investigation to (a) determine what is known about the magnitude of highway work zone crashes, (b) examine characteristics of highway work zone crashes using the Highway Safety Information System, (c) investigate how work zone accidents are reported on police ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…In terms of work zone rear-end crashes, a plethora of literature report the observation of an increased rate of rear-end crashes in work zones compared to nonwork zones [5][6][7][8][9]. Qi et al investigated rear-end crashes in the work zones and utilized the ordered probit model.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of work zone rear-end crashes, a plethora of literature report the observation of an increased rate of rear-end crashes in work zones compared to nonwork zones [5][6][7][8][9]. Qi et al investigated rear-end crashes in the work zones and utilized the ordered probit model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, it has been showed that rear-end collisions constitute 30% of all injuries and 29.7% of all property damage in the USA [4]. Additionally, it is also argued that rear-end crashes mostly occur on highway work zones rather than nonwork zones [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The work zone environment is volatile, often requiring abrupt lane changes and braking. Drivers may not maintain adequate situation awareness to notice these traffic changes in a work zone, leading to heightened risk of crashes (Wang, Hughes, Council, & Paniati, 1996). Typical work zone signs communicating risks or speed limits are not very effective in reducing speeds (Fontaine, Schrock, & Ullman, 2002).…”
Section: Work Zonesmentioning
confidence: 99%
“…However, the increased traffic conflicts cause higher rear‐end crash potential. Many past studies reported that the rates and frequency of rear‐end crashes in work zones are higher than those in non‐work zones . As deemed by Srinivasan et al .…”
Section: Introductionmentioning
confidence: 98%